Motivations behind end-of-life care: a qualitative study of Iranian nurses’ experiences - Zahra Royani; Khadijeh Yazdi; Gholam Reza Mahmoodi-Shan (BMC Palliative Care)
Abstract Background Providing high-quality end-of-life care is currently a paramount health priority. Given that the standard of care is intrinsically linked to nurses’ motivations, it is becoming too imperative to explore the contributing factors Consequently, this study was undertaken to elucidate the experiences of Iranian nurses regarding their motivation for delivering end-of-life care. Methods This research is a qualitative, descriptive inquiry employing conventional content analysis, carried out at two governmental hospitals in Gorgan, northern Iran, from February to July 2023. 12 nurses were purposefully selected to participate in the study, ensuring maximal diversity. The data were collected through semi structured interviews and analyzed using Graneheim and Lundman’s five-step method. The coding process was facilitated by the useof MAXQDA version 10 software. To establish rigor, the four criteria outlined by Guba and Lincoln were applied. Results the participants included eight women and four men with an average age of 39.6 ± 6.31 years. The data analysis yielded five main categories and fifteen subcategories. The main categories were: “The Foundations of professional care in nursing”, “Core Drivers in Optimal End-of-Life Care”, “Family Involvement in End-of-Life Care”, “Incorporating Spiritualism in Care” and “Dominant motivational Issues Within the Caregiving Atmosphere”. Conclusions This study delineates the experiences that influence the provision of end-of-life care from the perspective of Iranian nurses. Innate traits such as empathy and a passion for nursing, in addition to nurses’ moral compass and spiritual beliefs, serve as pivotal motivational stimuli. Leveraging these findings can be instrumental in shaping healthcare practices and policies to enhance the quality of end-of-life care.